2013
DOI: 10.1038/bmt.2012.261
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for a GVL effect following reduced-intensity allo-SCT in ALL: a British Society of Blood and Marrow Transplantation study

Abstract: Myeloablative allo-SCT decreases relapse incidence (RI) in ALL. Reduced intensity conditioning (RIC) may extend allo-SCT to older and less fit patients. Sixty-nine ALL patients reported to the BSBMT underwent fludarabine-based RIC allo-SCT, 38 from unrelated donors (UD). Forty-four patients received alemtuzumab. ALL was in CR in 64 patients (93%). This was a second or third SCT in 23 patients. Two-year OS and PFS were 36% and 32%, respectively. In multivariate analysis male recipients demonstrated better OS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Even earlier withdrawal of prophylactic immunosuppression has so far not led to a significant manifestation of adverse immunological complications. However, antileukemic control with GVL reaction [20], the main goal of this post-transplant approach, was apparently maintained in most patients in spite of high-risk and even very high-risk ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Even earlier withdrawal of prophylactic immunosuppression has so far not led to a significant manifestation of adverse immunological complications. However, antileukemic control with GVL reaction [20], the main goal of this post-transplant approach, was apparently maintained in most patients in spite of high-risk and even very high-risk ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [26,32,37,38,40,41,[66][67][68] also demonstrated that GVHD had a graft-versus-leukemia effect, but Grades III-IV aGVHD were accompanied by a higher NRM than cases without Grades III-IV aGVHD. [39,69] We also concluded that patients with Grades III-IV aGVHD had a higher NRM and poorer OS and LFS than those without Grades III-IV aGVHD, but there was no correlation with relapse.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, patients transplanted in ≥CR2 were more likely to be post-MRD positive than those in CR1 ( P = 0.016) in this study, which might be a reason why being in ≥CR2 was related to a higher CIR. Previous studies [ 26 , 32 , 37 , 38 , 40 , 41 , 66 – 68 ] also demonstrated that GVHD had a graft-versus-leukemia effect, but Grades III–IV aGVHD were accompanied by a higher NRM than cases without Grades III–IV aGVHD. [ 39 , 69 ] We also concluded that patients with Grades III–IV aGVHD had a higher NRM and poorer OS and LFS than those without Grades III–IV aGVHD, but there was no correlation with relapse.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other forms of RRT were mild and less frequent. In spite of relatively low general non-hematological toxicity, reduced combination of fludarabine and "high-dose" melphalan had significant myelosuppressive and immunosuppressive potential that allowed to achieve a stable engraftment of donor hematopoietic and immunocompetent cells responsible for GVL effect [7,16].…”
Section: Discussionmentioning
confidence: 99%